Acupuncture Legislation in Virginia, United States: A Personal Experience and Beyond - Arthur Yin Fan (Wolters Kluwer Health/LWW, 2022)
Virginia was once considered as one of three states in the United States that was particularly resistant to acupuncture and its legislation, due to the historically strong conservative force in Virginia. In this article, the author aims to review and discuss the history and the current situation of acupuncture legislation in Virginia, and provides some insights for the related legislations in other states and at federal level. This study was based on author's personal experience and an interview with Mr. Floyd Herdrich, former president of the Acupuncture Society of Virginia, who made the biggest contribution to this legislation. Led by the Acupuncture Society of Virginia, and supported by the School Tai Sophia Institute, Virginia acupuncture legislation began in 1988 and the law was implemented in 1994. Virginia is the 27th state in the United States to legalize acupuncture practice, and it has been 28 years since then. The author's insights are: the first important factor is dedications as the persistent efforts in legislation usually take many years to materialize. The second factor is the strategy, that is, legislation through the executive or administrative system is probably a much easier route or shortcut.